TEACHERS` SUPPORT SERVICE AS A PART OF FLEXIBLE EDUCATION CONCEPT: EXPERIENCE OF PR CHINA - Kalashnyk, Lyubov; Mkrtichan, Oksana; Zhukov, Kostiantyn; Marakushyn, Andrey (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In 2020 China became the first country of the world that faced all the challenges of the COVID-19 pandemic, including the ones that dealt with education. They were the first ones to provide lock-down and distance education as the only education reality as well as the first ones to face all the positive and negative repercussions of the process mentioned. That’s why the Chinese experience (both negative and positive) is worth presenting and exploring. There is one more peculiarity of the Chinese educational system that makes it unique and lets the country in a short period make a distance education system became competitive with the traditional off-line one. It is a teachers` support system that includes not only the teachers training system (vocational training activities), but also financial support for using different online-education tools, direct assistance of a group of specialists during preparing and lessoning, psychological support etc. The study aims to present the positive educational and organisation experience already approved in China. When writing the article, methods such as observation, study of normative and scientific literature were used for a comprehensive analysis of the new pedagogical reality - the teachers` support service.